1969
DOI: 10.1021/bi00831a055
|View full text |Cite
|
Sign up to set email alerts
|

Active swelling and acetate uptake in corn mitochondria

Abstract: Partially swollen corn mitochondria in KCI contract on addition of substrate, whereas in potassium acetate they show an additional swelling linked to respiration. Electron micrographs and gravimetric measurements confirm the volume changes measured by optical density methods. The effects of active swelling in acetate and other anions on respiratory control, volume changes, salt accumulation, and oxidative phosphorylation were determined. Active swelling is due to an inward transport of K+ and acetate accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1970
1970
1985
1985

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
(47 reference statements)
2
26
0
Order By: Relevance
“…The indifference to substrate suggests that it is the common coupling mechanism associated with electron transport which is responding. In the absence of an anion which will react with the coupling mechanism (e.g., phosphate) only efflux pumping of KCI (contraction) is seen (20), and here the only cation promotion of respiration is with exogenous Isolation of corn mitochondria with 5 mm EDTA improved respiratory control and resistance to aging at ice temperatures (Table III). Addition of 5 mM Mg2+ to the isolation medium had no effect, but when 50 mm phosphate was also added, respiratory control was high and the mitochondria were resistant to aging.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The indifference to substrate suggests that it is the common coupling mechanism associated with electron transport which is responding. In the absence of an anion which will react with the coupling mechanism (e.g., phosphate) only efflux pumping of KCI (contraction) is seen (20), and here the only cation promotion of respiration is with exogenous Isolation of corn mitochondria with 5 mm EDTA improved respiratory control and resistance to aging at ice temperatures (Table III). Addition of 5 mM Mg2+ to the isolation medium had no effect, but when 50 mm phosphate was also added, respiratory control was high and the mitochondria were resistant to aging.…”
Section: Methodsmentioning
confidence: 91%
“…Activation here lies with the coupling mechanism, and responses are obtained with all respiratory substrates. The postulated mechanism is one of active anion transport and is discussed fully in recent papers (8,10,17,20 (12) and general ATPase activity (13,17). This suggests that metals forming stable bonds are also required so that the time-dependent coupling necessary for ATPase can occur.…”
Section: Methodsmentioning
confidence: 98%
“…Phloem sieve tubes and some adjacent parenchyma cells contain (12,24,26). Swelling involves the unfolding of the inner membrane and a decrease in the amorphous matrix, while contraction involves the infolding of the inner membrane and increase in matrix density.…”
mentioning
confidence: 99%
“…It is generally thought that swollen corn mitochondria have very few cristae and a matrix that stains only lightly, that contracted mitochondria have many inflated cristae and a matrix that becomes densely stained, and that partially swollen mitochondria are intermediate (12,24,26). Swelling involves the unfolding of the inner membrane and a decrease in the amorphous matrix, while contraction involves the infolding of the inner membrane and increase in matrix density.…”
mentioning
confidence: 99%
“…Numerous studies (3,13,18,22) have demonstrated a passive, energy-independent swelling of plant mitochondria in the presence of isomolar salt solutions, or isomolar solutions of monosaccharide sugars. The existence of an energy-dependent (active) swelling component in plant mitochondria has also been demonstrated (2,5,19,21). Addition of certain oxidizable substrates to swollen mitochondria results in an immediate rapid contraction of the mitochondria while the addition of ATP initiates contraction of swollen corn mitochondria (18), but not swollen castor bean endosperm mitochondria (20).…”
mentioning
confidence: 94%